Expression, purification and structural characterisation of Hepatitis B virus core antigen with an N-terminal extension - Yoon, Kam Yee (2013)
Hepatitis B virus (HBV) belongs to the family of Hepadnaviridae which contains an enveloped, nucleocapsid consisting of multiple copies of core antigen (HBcAg). HBcAg expressed in Escherichia coli self assembles into large and small spherical particles with 240 (triangulation number T=4) and 180 (triangulation number T=3) HBcAg subunits, respectively. Previous X-ray analysis of the wild type HBcAg showed that the N-terminal region of HBcAg is displayed on the surface of the capsid but the additional 11 residues of β-galactosidase and a linker could only be observed with weak electron density in the absence of atomic features due to the low atomic resolution (~8.9Å). Previous purification of HBcAg particles performed with sucrose density gradient ultracentrifugation and gel filtration methods could not separate the large and small particles homogenously. Therefore, an improved method to purify and isolate the large and small HBcAg particles homogenously was developed using the native agarose gel electrophoresis and electro-elution method (NAGE-EE). Dynamic light scattering (DLS) and transmission electron microscopic analyses further confirmed the homogeneity of the purified and separated T=3 and T=4 HBcAg particles. However, the isolated T=3 and T=4 HBcAg particles could not produce the desired X-ray diffractable crystals for structural elucidation of HBcAg with an N-terminal extension. To improve the resolution, Tyr132 of the HBcAg polypeptide was substituted with an Ala (N-Y132A) in order to create a mutant that forms a dimer. The morphology of the dimer is similar to that of the HBcAg dimeric structure of the capsid. The mutant was expressed, purified and crystallised with 18% PEG 2,000, 200 mM calcium acetate and 100 mM sodium cacodylate, pH 6.5 at 291 K. Crystals soaked in 20% glycerol, which functions as a cryo-protectant, was diffracted with X-ray to a maximum resolution of 1.8 Å using synchrotron radiation sources. The crystal belongs to a space group P31 with the unit cell parameters a=103.86, b=103.86 and c=88.11 Å. The electron density map revealed the molecular details of the N-terminal extension displayed consistently on the surface of the nucleocapsid. Hence, this finding provides an insight into the N-terminal extension which may offer a route for the development of multicomponent vaccines and molecular carriers.